Redetermination of the crystal structure of bis{hydridotris(3,5-dimethylpyrazol-1-yl-κN3)borato} copper(II), C30H44B2CuN12 - Fujisawa, Kiyoshi; Okamura, M; Tiekink, Edward R. T. * (De Gruyter Open, 2022)
C30H44B2CuN12, triclinic, P1 (no. 2), a = 8.6801(1) Å, b = 10.1688(2) Å, c = 10.7290(2) Å, α = 62.672(2)°, β = 84.3550(10)°, γ = 78.9700(10)°, V = 825.71(3) Å3 , Z = 1,Rgt(F) = 0.0318, wRref(F2) = 0.0961, T = 178 K.